The new genus Symphyocladiella gen. nov. (Ceramiales, Rhodophyta) based on S. bartlingiana comb. nov. from the Pacific Ocean. Issue 1 (2nd January 2019) - Bustamante, Danilo E.; Won, Boo Yeon; Lindstrom, Sandra C.; Cho, Tae Oh
ABSTRACT: The number of species in the genus Symphyocladia was recently increased, with the majority of new species found in the Pacific Ocean. Based on molecular analysis, eight species of Symphyocladia formed a distinct clade sister to the clade containing the generitype Symphyocladia marchantioides . These eight species are transferred to a new genus Symphyocladiella, based on Symphyocladiella bartlingiana comb. nov ., a species that has not been reported since its original description and is herein described in detail. Diagnostic features that separate Symphyocladiella gen. nov . and Symphyocladia are the number of cell layers around rhizoidal tips at maturity and the degree of congenital fusion. Symphyocladiella has three- to five-celled filaments around rhizoidal tips and one to three segments of congenital fusion, whereas Symphyocladia has one- to two-celled filaments around rhizoidal tips and more than five segments of congenital fusion. Symphyocladiella gen. nov . is monophyletic with high support values and forms the sister group to Symphyocladia based on rbc L and the combined rbc L + cox 1 sequences.